Constraints on Genome Dynamics Revealed from Gene Distribution among the Ralstonia solanacearum Species - Lefeuvre, Pierre (Public Library of Science, 2013)
Because it is suspected that gene content may partly explain host adaptation and ecology of pathogenic bacteria, it is important to study factors affecting genome composition and its evolution. While recent genomic advances have revealed extremely large pan-genomes for some bacterial species, it remains difficult to predict to what extent gene pool is accessible within or transferable between populations. As genomes bear imprints of the history of the organisms, gene distribution pattern analyses should provide insights into the forces and factors at play in the shaping and maintaining of bacterial genomes. In this study, we revisited the data obtained from a previous CGH microarrays analysis in order to assess the genomic plasticity of the R. solanacearum species complex. Gene distribution analyses demonstrated the remarkably dispersed genome of R. solanacearum with more than half of the genes being accessory. From the reconstruction of the ancestral genomes compositions, we were able to infer the number of gene gain and loss events along the phylogeny. Analyses of gene movement patterns reveal that factors associated with gene function, genomic localization and ecology delineate gene flow patterns. While the chromosome displayed lower rates of movement, the megaplasmid was clearly associated with hot-spots of gene gain and loss. Gene function was also confirmed to be an essential factor in gene gain and loss dynamics with significant differences in movement patterns between different COG categories. Finally, analyses of gene distribution highlighted possible highways of horizontal gene transfer. Due to sampling and design bias, we can only speculate on factors at play in this gene movement dynamic. Further studies examining precise conditions that favor gene transfer would provide invaluable insights in the fate of bacteria, species delineation and the emergence of successful pathogens.